(untitled) (Global Journal of Science Frontier Research, 2022)
COVID-19 was declared a pandemic by the World Health Organization (WHO) in January 2020. Considering its unprecedented mortality and morbidity, a global lockdown was imposed worldwide which resulted in the halt of all economic and social activity. Most countries including India applied strict prevention and control measures to control the spread of COVID-19, which include general lockdown, obligatory home quarantine, a ban on public gatherings, international flight restrictions, etc. In this regard a KAP analysis was conducted to understand the public knowledge, reactions, adherence to, and acceptance of measures for protection against COVID-19 during first and second wave of Covid 19. Individuals above the age of 15 years were selected as the sample. The data were collected during both waves of the COVID-19 pan India from 500 respondents using a self-administered questionnaire in Google form. The results revealed that the majority of the respondents were knowledgeable regarding the spread, prevention and control of the COVID virus. Most of the respondents had positive attitude regarding control measures imposed by the government which was consistent with their attitude and practices during first wave. However, a negative change in the attitude of the respondents and practices despite rise in knowledge indicates the role of compelling variables like economic crisis, emotional crisis and individual’s reduced functioning.